Chaotic Secure Communication Schemes employing Chua's Circuit (2010)
In recent years, chaotic secure communication systems have attracted significant interest due to their higher unpredictability over conventional secure communications system and simplicity of implementation. This study presents the modeling of four chaotic modulation techniques. The techniques are Chaotic Masking (CM), Chaos Shift Keying (CSK), Chaos On-Off Keying (COOK), and Differential Choa Shift Keying (DCSK). Simulations were carried out using Simulink in Matlab environmnet to implement these techniques. A qualitative evaluation of the transmitted signal waveforms in all the cases considered showed that DCSK gives the highest level of secuirty followed by CSK while COOK gives the least level of security. The data transmission rate of the other three techniques was however twice that of DCSK.